PENGARUH MEKANISME TATA KELOLA PERUSAHAAN TERHADAP EFISIENSI MODAL INTELEKTUAL (Studi Empiris pada Perusahaan Jasa yang Terdaftar di Bursa Efek Indonesia Periode 2015 – 2017) - Myra Shafira Priyandani; Abdul Rohman (Diponegoro Journal of Accounting, 2019)
The study has the purpose to examine and analyze the influence of corporate governance mechanisms towards the efficiency of intellectual capital. The dependent variable of this research is the efficiency of intellectual capital (VAIC) and the independent variables are Board size, Board composition, and the independency level of Remuneration Committee.The population of this study consist of all service firms that listed in Indonesian Stock Exchange in 2015-2017 excluding the finance firms. Sample of this research is determined using purposive sampling and there are 164 samples that fulfill the criteria. This research is using multiple linear regression in order to test the data and hypotheses. The results show that not all the mechanism of corporate governance that be used in this research as independent variable such as Board size, Board composition, and the independency level of Remuneration Committee has significant influence toward the efficiency of intellectual capital.